The minimum amount of fluids needed to achieve the fastest time to reach permissible level for release in well-differentiated thyroid patients undergoing high-dose I-131 therapy - Cheen Hoe, Alex; Fong, Lee; Halim, Fatin; Fatt, Quek; Hamzah, Fadzilah (World Journal of Nuclear Medicine, 2018)
Radioiodine (131I) therapy is the mainstay of treatment for patients who had undergone total thyroidectomy for well differentiated thyroid carcinoma. Increased fluid intake has always been encouraged to minimize the risk of non-target organ exposure to I-131radiation. This study aimed to determine the minimum amount of fluids needed for patients to have the fastest time to achieve permissible level for release after high dose I-131therapy. Methodology: All the patients who were treated with high dose I-131from 18th January 2016 till 31st December 2016 in Hospital Pulau Pinang, Malaysia were recruited. The data from 126 patients on thyroxine hormone withdrawal (THW) group and 18 patients on recombinant human thyroid stimulating hormone (rhTSH) group were analysed. There is no change in patient management in terms of preparation, dose or post therapy whole-body scan. Fluid intake of patients were monitored strictly and whole-body retention of I-131are measured using ionizing chamber meter immediately after ingestion of I-131then at 1 hour, 24 hours, 48 hours, 72 hours and 96 hours. Results: The median time to achieve permissible release limit (50 μSV/hr at 1 meter) was 21.6 hours and 22.1 hours post-ingestion of I-131in the THW and rhTSH group respectively. The minimum amount of fluid needed to reach permissible release limit in the fastest time was 2,103 ml and 2,148ml for the THW and TSH respectively. Conclusion: Clinicians would be able to evidently advise their patient on the amount of fluid to consume and utilize their isolation wards faster to treat more patients.
Keywords: Differentiated thyroid cancer; fluid; I-131; whole body retention